Strength assessment of structural size Malaysian timbers / Mohd Jamil Abdul Wahab - Mohd Jamil , Abdul Wahab (2013)
Existing strength data of Malaysian timbers are based on mechanical tests of small clear specimen. The formal mechanical properties assessment of timber in structural sizes has not been carried out for most tropical species, including Malaysian timbers. The present study is a groundwork testing on some selected commercial timbers to develop correlation factors between structural size and small clear specimens of timber in bending. A total of 120 planks of mixed species of Malaysian hardwoods were cut into standard sizes for structural size bending test as mentioned in EN 408:2003 and small clear specimen of 50 mm by 50 mm (2 inches by 2 inches) size according to ASTM D143 - 52. The ultimate results of MOR and MOE between the two testing methods were evaluated. Weak MOR correlation was observed between small clear and structural specimens. MOE relationship was shown to be consistent even for unconditioned and ungraded specimens. However, the risk of inaccurate deflection measurement is much higher for MOE in structural test. The developed correlation factors are then applicable for the data conversion of timbers in similar strength group where only small clear data exist. A robust statistical technique was introduced to group the Malaysian timbers into similar strength classes. The grouping is intended to simplify the conversion work of the existing strength data to equivalent structural size values.